PERCENTAGE OF FAT AND MAXIMUM OXYGEN CONSUMPTION: AN ASSOCIATION OF PHYSICAL FITNESS VARIABLES OF SOCCER PLAYERS (Fiep Bulletin - online, 2014)
The percentage of fat (%BF) and the maximum oxygen consumption (VO2max) are presented as important variables to be highlighted mainly in soccer players, since the levels of physical fitness might influence in a faster recovery of intense exercise characteristic of the game. Given these issues,, the present study aims to analyze the correlation of %BF and VO2max of soccer players of two teams in the countryside of Rio Grande do Sul, who competed in the series A and B of the state championship, professional category. It is a comparative cross-sectional study conducted with users of the “Functional Assessment for the Community”, project in the Laboratory of Health and Physical Activities (LAFISA). Were evaluated 55 male athletes with average age of 24.9 ±4.9 years, of different positions in soccer, divided in two groups: A and B, respectively to the series they were competing. The variables assessed were: %BF through the predictive equation of Jackson and Pollock, using seven skinfolds; VO2max obtained with an incremental stress test done by the Bruce protocol, on a treadmill using a gas analyzer VO2000. The data was tabulated and analyzed using the program Statistical Package for Social Sciences for Windows (SPSS – version 20.0), through descriptive statistics and the correlation test Pearson, considering p?0.05. The results showed a regular and inverse relationship between the variables analyzed (%BF and VO2max), for both evaluated teams (A: r= -,475; B: r=-,0425), indicating that the higher the values of %BF, lower were the values for VO2max. Despite these differences, for both groups it was identified the relationship between the variables analyzed indicating the importance of the influence of body fat in cardiorespiratory capacity.
Keywords: body composition; oxygen consumption; soccer athletes